Mutanome directed cancer immunotherapy. (April 2016) - Vormehr, Mathias; Diken, Mustafa; Boegel, Sebastian; Kreiter, Sebastian; Türeci, Özlem; Sahin, Ugur
Highlights: Mutated antigens are major targets of spontaneous and immunotherapy-induced T-cell responses. Mutation abundance correlates with the success of checkpoint blockade and adoptive T-cell transfer. High-throughput mutation identification enables personalized immunotherapies. Abstract : Somatic mutations are important drivers of cancer development. Accumulating evidence suggests that a significant subset of mutations result in neo-epitopes recognized by autologous T cells and thus may constitute the Achilles' heel of tumor cells. T cells directed against mutations have been shown to have a key role in clinical efficacy of potent cancer immunotherapy modalities, such as adoptive transfer of autologous tumor infiltrating lymphocytes and immune checkpoint inhibitors. Whereas these findings strengthen the idea of a prominent role of neo-epitopes in tumor rejection, the systematic therapeutic exploitation of mutations was hampered until recently by the uniqueness of the repertoire of mutations ('the mutanome') in every patient's tumor. This review highlights insights into immune recognition of neo-epitopes and novel concepts for comprehensive identification and immunotherapeutic exploitation of individual mutations.